2012
DOI: 10.1136/annrheumdis-2012-201627
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146aandEts-1gene polymorphisms in ocular Behçet's disease and Vogt–Koyanagi–Harada syndrome

Abstract: Our study identified a strong association of rs2910164 of miR-146a with BD in a Chinese population and decreased expression of miR-146a and certain proinflammatory cytokines in individuals carrying the CC genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 37 publications
3
58
1
2
Order By: Relevance
“…This form of miRNA dysregulation was demonstrated in Han Chinese BD patients in miR146a/rs2910164, miR-196a2/rs11614913, and miR-182/ rs76481776 (Table 3). In the first study, BD was associated with variant rs2910164 within miR-146a, a key regulator of the type I interferon pathway [62,63]. Healthy individuals with the homozygous risk allele for miR-146a/rs2910164 had increased miR-146a expression and increased serum levels of pro-inflammatory cytokines IL-1β, IL-17, and tumor necrosis factor alpha (TNF-α).…”
Section: Behçet's Diseasementioning
confidence: 98%
“…This form of miRNA dysregulation was demonstrated in Han Chinese BD patients in miR146a/rs2910164, miR-196a2/rs11614913, and miR-182/ rs76481776 (Table 3). In the first study, BD was associated with variant rs2910164 within miR-146a, a key regulator of the type I interferon pathway [62,63]. Healthy individuals with the homozygous risk allele for miR-146a/rs2910164 had increased miR-146a expression and increased serum levels of pro-inflammatory cytokines IL-1β, IL-17, and tumor necrosis factor alpha (TNF-α).…”
Section: Behçet's Diseasementioning
confidence: 98%
“…Li et al demonstrated that ApoE regulates the expression of miR-146a in monocytes and macrophages to repress NF-B signaling in these cells, and intravascular delivery of miR-146a mimetics can inhibit atherogenesis in mouse models 13) . However, the 4 gene polymorphism causes strong dysfunction of ApoE, which suppresses the level of miR146a 13,38,50) . Based on the finding that ApoE 4 induced decreasing expression of miR-146a in ACI patients, we suggest that the downregulation of NF-B-dependent pathways by miR-146a through a critical negative feedback regulatory loop was attenuated by the effects of ApoE 4.…”
Section: The Influence Of Apoe 4 On Mir-146a Expression In Aci Patientsmentioning
confidence: 99%
“…In our study, two functional SNPs in miR-146a were chosen to evaluate the association between miR-146a polymorphisms and ACI risk. The two SNPs in miRNA-146a, rs2910164 and rs57095329, have been reported to influence the expression level of mature miR-146a; thus, these SNPs may ultimately affect an individual's susceptibility to disease 10,37,38) . Our results revealed that the rs2910164 polymorphism was associated with an increased risk of ACI; the C allele of rs2910164 was more frequent in patients with ACI compared with the G allele, indicating that the C allele of rs2910164 is associated with an increased risk of ACI susceptibility.…”
Section: The Influence Of Apoe 4 On Mir-146a Expression In Aci Patientsmentioning
confidence: 99%
“…[15][16][17] Many studies [18][19][20][21][22][23] have demonstrated that miRNAs play a role in pathogenesis of human autoimmune and autoinflammatory diseases such as Behcet's disease (BD) and AS. Earlier studies 22 have shown that the miR-146a rs2910164 CC genotype and C allele confer risk for BD. Having more than two gene copies of miR-23a, miR146a, and miR-301a has been shown to be linked to the susceptibility to Vogt-Koyanagi-Harada (VKH) syndrome.…”
Section: Discussionmentioning
confidence: 99%